Pelatihan Analisis SWOT dan BMC (Business Model Canvas) pada Santri di Pondok Pesantren Al Mumtaz - H, Nurlina (Program Studi Kehutanan, Universitas Khairun, 2025)
Islamic boarding schools as Islamic educational institutions have great potential in developing entrepreneurship. However, many Islamic boarding schools still have limitations in business management and business planning. This training aims to provide SWOT Analysis and BMC (Business Model Canvas) training to students through mentoring at WEIPA (Al Mumtaz Preneurship Inspiration Education Tour) at Al Mumtaz Islamic Boarding School. This training is an effort to support the independence of Islamic boarding schools which is realized by the existence of business ventures at the Islamic Boarding School. Therefore, this training was held to facilitate WEIPA management in developing business strategies who are also students at the Islamic Boarding School and there are 20 Agribusiness Study Program Students who carry out Social Laboratory activities that assist WEIPA management. The implementation method includes initial observation, training, and evaluation of activities. The results of this training provide an overview of the increased understanding of participants regarding the strengths, weaknesses, opportunities and threats at WEIPA, as well as the ability to develop simple business models using BMC. This training activity is expected to be the first step towards the economic independence of Islamic boarding schools.